Análisis de crianza y reproducción de la lombriz roja californiana (Eisenia foetida) - Guevara Villamar, Luis Fernando (2024)
The present study focuses on analyzing the breeding and reproduction of the California red worm (Eisenia foetida), a species of worm used in vermicomposting due to its high capacity for organic matter decomposition. An experiment was conducted under controlled conditions to evaluate different parameters related to the breeding and reproduction of these worms. Factors such as temperature, humidity, substrate type, and population density were examined to determine their influence on worm growth and reproduction. The results indicate that the optimal temperature for the breeding and reproduction of the California red worm is approximately 20-25°C, with substrate humidity of 70-80%. A higher reproduction rate was observed in substrates composed of organic matter, especially manure and vegetable waste. It was also found that moderate population density favors worm reproduction and growth. These findings provide valuable information for improving vermicomposting practices and promoting the sustainable use of the California red worm in agriculture and waste management.